EVOLUTIONARY RELATIONSHIP OF THE EOCENE DIATOM FLORA TO SOME ABIOTIC FACTORS - Gleser Z.I. (My University, 1996)
The Eocene evolution of the diatom flora of oceanic and epicontinental sea basins is discussed within the context of some abiotic factors. It was found that from the beginning of the Eocene to the end of the Lutetian, the flora of the Eurosiberian type was widely spread, and the flora of the Atlantic type began to progress from the middle of the early Miocene to reach its prosperity at the end of the Lutetian and the beginning of the Bartonian. The evolution of the flora in basins was controlled by the migration of biogenic elements into the euphotic zone, which in turn, depended upon volcanic activity, transgressions, climate, and lateral and vertical currents. The taxonomic composition of the flora in separate basins is a reflection of a combined effect of global and local factors on evolutionary and migration processes.
Keywords: Eocene; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен